Δημογραφική μετάβαση και δημογραφικό πρόβλημα της Ελλάδας: θεωρητικοί και μεθοδολογικοί προβληματισμοί - Μπαλούρδος, Διονύσης (The Greek Review of Social Research, 1997)
This paper examines the basic mechanisms behind the historical changes of demographic behavior in Greece, within the analytical framework of the demographic transition theory. The several phases of the demographic transition are distinguished clearly and illustrated following a simplified classic diagrammatic presentation. Underlying clearly, Greece having experienced all successive stages of the classical demographic transition theory is currently faced with a new demographic situation, which is characterised by population aging and low fertility rate. These two distinct population characteristics constitute the core demographic problem in Greece. The above mentioned characteristics were first observed in the early 1970s and 1980s, which coincide with the early phases of economic recession and crisis. Many scholars intended to be alarmists about the implications of falling birth rates and demographic aging. Others, using different population indexes and criteria, were more optimistic in their motivations, calculations and predictions.